Quality gaps identified through mortality review. Issue 2 (8th February 2016) - Kobewka, Daniel M; van Walraven, Carl; Turnbull, Jeffrey; Worthington, James; Calder, Lisa; Forster, Alan
Abstract : Background: Hospital mortality rate is a common measure of healthcare quality. Morbidity and mortality meetings are common but there are few reports of hospital-wide mortality-review processes to provide understanding of quality-of-care problems associated with patient deaths. Objective: To describe the implementation and results from an institution-wide mortality-review process. Design: A nurse and a physician independently reviewed every death that occurred at our multisite teaching institution over a 3-month period. Deaths judged by either reviewer to be unanticipated or to have any opportunity for improvement were reviewed by a multidisciplinary committee. We report characteristics of patients with unanticipated death or opportunity for improved care and summarise the opportunities for improved care. Results: Over a 3-month period, we reviewed all 427 deaths in our hospital in detail; 33 deaths (7.7%) were deemed unanticipated and 100 (23.4%) were deemed to be associated with an opportunity for improvement. We identified 97 opportunities to improve care. The most common gap in care was: 'goals of care not discussed or the discussion was inadequate' (n=25 (25.8%)) and 'delay or failure to achieve a timely diagnosis' (n=8 (8.3%)). Patients who had opportunities for improvement had longer length of stay and a lower baseline predicted risk of death in hospital. Nurse and physician reviewers spent approximately 142 h reviewing cases outside of committee meetings. Conclusions: Our institution-wide mortality review found many quality gaps among decedents, in particular inadequate discussion of goals of care.